The role of banks in the provision of low‐income housing finance in South Africa: Can they play a different role? - Kajimo‐Shakantu, Kahilu; Evans, Kathy (International Journal of Strategic Property Management, 2010)
Currently, South African banks exclude most low‐income households from access to formal housing loan finance with which to resolve housing problems. The research reported here examined the banks’ resilience to change the status quo so as to become more flexible and all‐inclusive. Using naturalistic enquiry, the research gathered evidence from five banks and a leading housing organisation. The main findings include that while there is potential for banks to expand their role in this area of housing finance; factors such as risk and cost minimisation as well as lack of research constrain this potential. The research concluded that the low‐income group requires a different business model that is suited to their needs and which calls for new ways of thinking and doing business. First Published Online: 18 Oct 2010